Reflections of a Rural Practitioner - Malone, Judi L. (Canadian Journal of Counselling and Psychotherapy, 2010)
Some ethical dilemmas are more prevalent or more complicated to resolve in rural practice. In this practice note, I share some of the reflections that have helped me to unpack some of the ethical complications of overlapping relationships and objectivity, community pressure and integrity, generalist practice and competency, interdisciplinary collaboration and confidentiality, and professional development and support in rural professional practice.